1992
DOI: 10.1093/nar/20.7.1587
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the rat ribosomal DNA promoter: characterization of linker-scanning mutants and of the binding of UBF

Abstract: To investigate the mechanism of transcription of the rat ribosomal DNA (rDNA) promoter, a series of 23 linker-scanning mutants were constructed and assayed in transfected CHO cells and with cell-free extracts. With minor variation, the results of the in vitro and in vivo assays paralleled one another. For example, these assays demonstrated that the mutagenesis of bases from -133 to -124, and those from -106 to -101 of the rDNA promoter significantly inhibited transcription both in vivo and in vitro. Both of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…2A, lane 3). These findings confirm previous studies that have demonstrated that the guanine at -7 is essential for transcription by RNA polymerase I from the 45S promoter in vivo (34). They also indicate that the expression of pSMECAT must to be due to transcription by RNA polymerase I rather than spurious initiation from cryptic polymerase II or III promoters.…”
Section: Methodssupporting
confidence: 91%
“…2A, lane 3). These findings confirm previous studies that have demonstrated that the guanine at -7 is essential for transcription by RNA polymerase I from the 45S promoter in vivo (34). They also indicate that the expression of pSMECAT must to be due to transcription by RNA polymerase I rather than spurious initiation from cryptic polymerase II or III promoters.…”
Section: Methodssupporting
confidence: 91%
“…Each rDNA unit consists of a transcribed sequence and an external non-transcribed spacer (Hadjiolov 1985 ; Liau and Perry 1969 ) in which all the sequences necessary for proper RNA pol I transcription such as proximal promoters, spacer promoters and terminators are located (Hadjiolov 1985 ). In the rDNA promoter two important elements have been described, a CORE element and an upstream control element (UCE) (Haltiner et al 1986 ; Windle and Sollner-Webb 1986 ; Xie et al 1992 ) that function synergistically to recruit a transcriptionally competent RNA pol I complex. This complex contains in addition to RNA pol I, the upstream binding factor (UBF) (Pikaard et al 1989 ; Voit et al 1992 ), the selectivity factor protein complex SL1 (Learned et al 1985 ) also called TIF-1B in mouse cells (Clos et al 1986 ), consisting of the TATA-binding protein (TBP) and four transcription activating factors [TAF I s110, 63, 48 and 41 (Comai et al 1994 ; Gorski et al 2007 ; Zomerdijk et al 1994 )], the transcription initiation factor TIF-IA, the mouse homolog of Rrn3p (Bodem et al 2000 ; Moorefield et al 2000 ) and the transcription termination factor TTF-1 (Bartsch et al 1988 ).…”
Section: Control Of Rdna Transcription During Cell Cyclementioning
confidence: 99%
“…pSMECAT-7 was used in place of pSMECAT in some experiments. pSMECAT-7 contains a G to A substitution at 77 in the rDNA promoter which inhibits transcription by RNA polymerase I (Xie et al, 1992). Thus, pSMECAT-7 is a control for the possibility that CAT expression results from transcription by RNA polymerase II or RNA polymerase III.…”
Section: Transfections and Cat Assaysmentioning
confidence: 99%
“…These proteins are generated by alternative splicing of the transcripts of one gene (Hisatake et al, 1991;O'Mahony and Rothblum, 1991;Putnam and Pikaard, 1992;Kuhn et al, 1994;Paule, 1994). UBF is not absolutely required for speci®c initiation on the rDNA promoter in vitro, although its addition to UBFdepleted extracts increases the eciency of transcription in a dose dependent manner (Jantzen et al, 1990;Xie et al, 1992;Smith et al, 1990;1993). In addition, overexpression of UBF1 in either immortal cells or primary cultures of cardiomyocytes is sucient to directly increase transcription of a reporter for rDNA transcription (Hannan et al, 1996b;.…”
Section: Introductionmentioning
confidence: 99%